2015
DOI: 10.1177/2045125315590060
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced stuttering: an estimate of prevalence in the west of Ireland

Abstract: Objectives: Clozapine is the most effective treatment available for treatment-resistant schizophrenia; however, it is also associated with a large array of adverse effects that limits its tolerability. A number of previous case reports have noted an association between clozapine and stuttering, however the rate of this possible adverse effect is yet to be established. Methods: In this paper, we present six cases of patients treated with clozapine who developed stuttering. Results: Clozapine was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…While our case also showed seizure-like activity on an EEG that corresponded to the patient's stuttering, there is a discrepancy in the current literature about the etiology of the stuttering. Murphy et al reported that most of the clozapine-induced symptoms resolved without any antiepileptic treatment and two patients with clozapine-induced seizures showed no EEG abnormalities [ 4 ], although a lack of EEG changes does not necessarily preclude the diagnosis of seizures in a clinical setting. The role of antiepileptic pharmacotherapy in cases of clozapine-induced stuttering remains yet unclear, although antiepileptic therapies may have a role in preventing tonic-clonic seizures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While our case also showed seizure-like activity on an EEG that corresponded to the patient's stuttering, there is a discrepancy in the current literature about the etiology of the stuttering. Murphy et al reported that most of the clozapine-induced symptoms resolved without any antiepileptic treatment and two patients with clozapine-induced seizures showed no EEG abnormalities [ 4 ], although a lack of EEG changes does not necessarily preclude the diagnosis of seizures in a clinical setting. The role of antiepileptic pharmacotherapy in cases of clozapine-induced stuttering remains yet unclear, although antiepileptic therapies may have a role in preventing tonic-clonic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…The potential to cause microseizures may be increased not only with a high dose but also with quicker titration. Murphy et al reported that several patients developed stuttering when their dosage was titrated too rapidly or the target dose was too high and the symptoms resolved with a reduction of the dose by 25–50 mg or with a slower titration schedule [ 4 ]. However, they also reported that one of the patients developed stuttering without any changes in the medication regimen and a dose reduction resulted in no change in the side effect but a recurrence of their psychosis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study in Ireland estimated the prevalence of stuttering as 0.92% (6 of 654) in patients treated with clozapine. [7]…”
Section: Discussionmentioning
confidence: 99%
“…Stuttering happens due to rapid titration of dose and higher dose and presence of multiple drugs leading to drug interactions. [ 4 6 ]…”
Section: Clozapine-induced Stuttering: Causationmentioning
confidence: 99%